Documenting challenges in achieving rabies elimination by 2030 in low-middle income countries; a Kenyan case study from Lamu County, 2020–2022: mixed methods approach - Mwanyalu, N.; Mwatondo, Athman; Chuchu, V.; Maina, K.; Muturi, Mathew; Mutiiria, M.; Chepkwony, D.; Owiny, M.; Munyua, P. (BioMed Central, 2025)
Background: Kenya launched a Rabies Elimination Strategy in 2014, aiming to end human rabies deaths by 2030. In March 2022, Lamu County reported increased cases of human dog bites and suspected rabies deaths to the Ministry of Health (MoH). We aimed to establish the extent of the rabies outbreak in humans and animals and determine the challenges to achieving rabies elimination by 2030.